Reflecting on the Role of the Arctic Council vis-à-vis a Future International Legally Binding Instrument on Biodiversity in Areas Beyond National Jurisdiction - De Lucia, Vito; Nickels, Philip Peter (Arctic Review on Law and Politics, 2020)
Negotiations are ongoing to develop an international legally binding instrument (ILBI) under the United Nations Convention on the Law of the Sea (UNCLOS) on the conservation and sustainable use of marine biological diversity in areas beyond national jurisdiction (BBNJ). If adopted, the ILBI will likely apply to parts of the Arctic Ocean where the Arctic Council has played an important role for ocean governance. This begs the question of what role the Arctic Council will play vis-à-vis a future ILBI, which is envisioned to “not undermine existing relevant legal instruments and frameworks and relevant global, regional and sectoral bodies” (UN General Assembly Resolution 72/249). Against this backdrop, this article reflects on the future relationship between the Arctic Council and the ILBI. In so doing, the article initially discusses possible meanings of the notion of not undermining and, more broadly, how the ILBI will likely determine its institutional relationship with relevant bodies for BBNJ. Based on that, the article provides a short overview of the role of the Arctic Council in Arctic Ocean governance and explores whether the Arctic Council would qualify as a relevant regional body that shall not be undermined by the future ILBI.